Antifungal effect against wilting disease factor Verticillium dahliae Kleb. by green synthesized silver nanoparticles - Alp Cokislerel; Melisa Ayisigi; Yigit Kucukcobanoglu; Pervin Gunturkun; Lale Yildiz Aktas (Exploration of BioMat-X, 2025)
Aim: This study aimed to synthesize, characterize, and evaluate the antifungal efficacy of green-synthesized silver nanoparticles (AgNPs) against Verticillium dahliae Kleb., a soil-borne fungal pathogen that affects numerous crops. Methods: AgNPs were synthesized using Laurus nobilis L. (laurel) leaf extract. The synthesized AgNPs were characterized using UV-VIS spectroscopy, Fourier-Transform Infrared Spectroscopy (FTIR), zeta potential, particle size analysis (PSA), and scanning electron microscopy (SEM). In vitro antifungal assays were conducted to assess the impact of AgNPs on V. dahliae mycelial growth, and SEM was used to examine the morphological changes in treated mycelium. Results: UV-VIS spectroscopy confirmed AgNP synthesis with a characteristic SPR peak between 400–450 nm. FTIR analysis identified the presence of phenolic compounds on the nanoparticle surface. Zeta potential analysis (–27.7 mV) indicated stable dispersion. Zeta size analysis indicated an average diameter of approximately 100 nm and a polydispersity index (PdI) of 0.229. SEM imaging confirmed a predominantly spherical morphology and PSA revealed a size range of 14–34 nm, with an average diameter of 24 nm. In vitro antifungal assays showed significant inhibition of V. dahliae mycelial growth, with radial mycelial growth reduced to 2.75 cm compared to 4.8–6.4 cm in the control group after 14 days. SEM imaging of treated mycelium revealed pronounced morphological damage, including collapse and shrinkage of hyphae and spores. Conclusions: Green-synthesized AgNPs using L. nobilis leaf extract demonstrated significant antifungal activity against V. dahliae. The observed inhibition of mycelial growth and morphological damage suggests the potential of these AgNPs as a sustainable and eco-friendly alternative for managing this fungal pathogen. The antifungal mechanism may involve membrane disruption, increased permeability, oxidative stress, and the inactivation of cellular components.